Distinct dietary alpha-linolenic acid-dependent shifts in the fecal microbiome composition suppresses aging-associated inflammatory responses and thrombus formation. (25th November 2020) - Saeedi Saravi, S.S; Bonetti, N.R; Camici, G.G; Luscher, T.F; Beer, J.H
Abstract: Background: Aging is associated with alterations in the fecal microbiome composition. The microbiota-derived trimethylamine-N-oxide (TMAO) correlates with arterial thrombotic events, e.g. myocardial infarction and stroke, the leading causes of mortality worldwide. The omega-3 fatty acid (n-3 FA) α-linolenic acid (ALA) has been shown to be protective against thrombosis and associated pathologies. Therefore, we hypothesized that long-term dietary ALA supplementation protects against the aging-associated microbiome dysbiosis, and reduces inflammatory and thrombotic responses. Methods: 24 week-old male C57BL/6 mice were fed either a high ALA (7.3g%) or low ALA (0.03g%) diet for 12 months. We examined the compositional changes of fecal microbiota of the animals treated with high vs. low ALA via 16S rRNA gene sequencing. The plasma levels of TMAO and its precursors choline and betaine, and LPS were measured by ELISA. Additionally, the platelet aggregation in response to thrombin, and thrombus formation on collagen under high-shear flow conditions of 3000/sec (to mimic blood flow in stenosed arteries) were investigated. Results: Genomic analyses showed that the abundance of Phylum Proteobacteria and the family of desulfovibrio were reduced 71.72% and 51.73% in the aged high ALA-treated mice (p<0.01 and p<0.001, resp.) that may result in decrease in TAMO production and the subsequent inflammatory responses. However, microbial diversity of Bacteroidetes or Fermicutes and Bacteroidetes/Fermicutes ratio did not demonstrate a significant change between high vs. low ALA groups. Interestingly, the dietary intake of high ALA increased the abundance of Lachnospiraceae (p<0.01) that may exert anti-inflammatory effects. Importantly, high ALA significantly decreased the plasma levels of TMAO (p<0.01) and its precursor choline (P<0.05), but not betaine. The pro-inflammatory cytokine TNF-α showed a significant reduction (p<0.05), whereas plasma IL-1β did not change significantly following high ALA supplementation. An increased thrombus formation on collagen under high-shear flow (36.34%, p<0.01) and thrombin-induced platelet aggregation (31.31%, p<0.05) were found in the aged mice. Conclusion: These studies demonstrate that an ALA-rich diet induces beneficial bacterial shifts in the aging-associated fecal microbiome that may lead to the suppression of inflammatory and thrombotic responses. Hence, long-term dietary ALA supplementation may be exploited as a nutritional antithrombotic strategy in the aging. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Swiss National Science Foundation (SNSF)